Foyle's war. Set 3 [videorecording (DVD)] - Millar, Gavin; Silberston, Jeremy; Kitchen, Michael, 1948-; Howell, Anthony, 1971-; Weeks, Honeysuckle, 1979-; Ovenden, Julian; Redgrave, Corin; Paterson, Bill, 1945-; Gonet, Stella; West, Samuel, 1966-; Wilby, James (Distributed by Acorn Media, 2009)
Set in 1941, as World War II rages over Europe, Michael Kitchen stars as detective Christopher Foyle, whose loyalties are put to the test as his investigations uncover unpleasant truths that powerful people would rather keep hidden.